Diagnosis Sarkopenia pada Geriatri Menggunakan Akselerometer Actigraph wGT3XBT: Tinjauan Naratif: Analisis - Mahardhika, Gembong Satria; Hurulhanifa, Fatmanur; Laranti, Nimas Adiani Sekar; Shabrina, Hanifa Nur; Agatri, Norina (PT Kalbe Farma Tbk., 2025)
Sarcopenia is a degenerative condition of age-related decline in muscle mass and strength. The worldwide occurrence of sarcopenia varied from 8% to 36% in those under the age of 60, and from 10% to 27% in those aged 60 and above. There is 9.92% or around 26.82 million, elderly people in Indonesia. Several studies have stated that in 2020, the incidence of sarcopenia in Indonesia ranged from 9.1% to 59%. Various studies have shown that accelerometers can provide a quantitative measurement of physical activity, positively correlated with muscle mass and strength in the elderly. Accelerometers, particularly the Actigraph wGT3X-BT, offer an objective approach to measuring physical activity and provide important insights into sarcopenia. Accelerometers offer an unbiased method for quantifying physical activity, offering valuable information on sarcopenia, and serving as a clinical diagnostic tool for this disorder characterized by reduced muscle mass and function. Literature review suggests that the Actigraph wGT3X-BT accelerometer has great potential for early detection and diagnosis of sarcopenia. The integrated use of this technology is expected to improve the accuracy of diagnosis and enable more effective interventions, thereby improving the quality of life of the elderly in Indonesia.